The origin of the brittleness of high aluminum pearlite and the method for improving ductility. (November 2016) - Chen, P.; Xiong, X.C.; Wang, G.D.; Yi, H.L.
Abstract: High aluminum bearing steels demonstrate poor ductility due to the presence of κ-pearlite in the as hot-rolled condition. The addition of aluminum shifts the equilibrium eutectoid carbon concentration to a higher value. Consequently, the poor ductility of high aluminum pearlite is believed to originate from the brittleness of κ-pearlite due to the higher fraction of brittle κ-carbide. The spheroidization treatment of κ-carbide is proposed and proven for the first time to improve the ductility by reducing the stress concentration at the carbide/ferrite interface and enhancing the cracking resistance of κ-carbide due to its spheroidized morphology. Graphical abstract: